2020
DOI: 10.2340/16501977-2627
|View full text |Cite
|
Sign up to set email alerts
|

International Classification of Service Organization in Rehabilitation: An updated set of categories (ICSO-R 2.0)

Abstract: Rehabilitation services should be available worldwide for every person who has problems with functioning. Thus, rehabilitation services must be organized at all levels of healthcare, from the community, through primary care to general and specialized hospitals. Rehabilitation services are needed along the continuum of care: from acute, through post-acute to the chronic phase. In order to plan these services a classification system is needed to describe, in a uniform way, the different types of services and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 22 publications
1
48
0
3
Order By: Relevance
“… To further develop the skills and competencies of already trained physiotherapists, it is recommended to develop standards for physiotherapy for different conditions and services based on the best available evidence (mean score: 1.09). Develop standards for staffing and technical equipment for specific rehabilitation services (mean score: 1.33) To learn about the existing rehabilitation services in the country, a rehabilitation service survey in the country that is based on the International Classification of Service Organization in Rehabilitation (ICSO-R) can be implemented [ 24 , 25 ] (mean score: 1.25). As some of the above projects will require financial support, it is important to develop a funding strategy for such projects ( Charity funding, use existing national research funds, apply for European Union funds ) (mean score: 1.42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… To further develop the skills and competencies of already trained physiotherapists, it is recommended to develop standards for physiotherapy for different conditions and services based on the best available evidence (mean score: 1.09). Develop standards for staffing and technical equipment for specific rehabilitation services (mean score: 1.33) To learn about the existing rehabilitation services in the country, a rehabilitation service survey in the country that is based on the International Classification of Service Organization in Rehabilitation (ICSO-R) can be implemented [ 24 , 25 ] (mean score: 1.25). As some of the above projects will require financial support, it is important to develop a funding strategy for such projects ( Charity funding, use existing national research funds, apply for European Union funds ) (mean score: 1.42).…”
Section: Resultsmentioning
confidence: 99%
“…To learn about the existing rehabilitation services in the country, a rehabilitation service survey in the country that is based on the International Classification of Service Organization in Rehabilitation (ICSO-R) can be implemented [ 24 , 25 ] (mean score: 1.25).…”
Section: Resultsmentioning
confidence: 99%
“…34 Finally, local and global stakeholders' awareness has emerged only recently for the need to monitor, plan and develop rehabilitation resources, in tandem with the growing awareness of population ageing and the increasing rates of chronic conditions, disabilities, and corresponding physical rehabilitation needs. 3,14,20,[35][36][37][38] Within the 35 HICs, great disparities were found for the OTs and PTs supply per capita, eg, up to 40 times the difference. Our inferential analysis showed that such a disparity was not explained by varying need levels; the latter had a more sensible variation, eg, up to 2.5 times the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Im Modell des "functioning" der Weltgesundheitsorganisation können solche Faktoren dem Bereich der Kontextfaktoren zugeordnet werden, die, wie diese wenigen Beispiele zeigen, nicht nur die Körperfaktoren, Aktivitäten und Teilhabe beeinflussen, sondern auch die durchgeführten Therapie-und Rehabilitationsmaßnahmen. Beispiele [5], die eine standardisierte Analyse der Versorgungsstrukturen ermöglicht und auch geeignet ist, für die Therapie und Rehabilitation relevante Kontextfaktoren zu erfassen [6].…”
Section: Klinische Entscheidungen In Der Physikalischen Und Rehabilitativen Medizinunclassified